2020
DOI: 10.3390/jcm9051531
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Febrile Children with Sickle Cell Disease Who Present to the Emergency Room with Fever

Abstract: Sickle cell disease (SCD) patients are thought to be at higher risk for urinary tract infections (UTIs) compared to the general population secondary to increased sickling, abnormal urinary acidification, and an inability to concentrate the urine. The incidence of UTI in febrile children with SCD in the United States is unknown. Our objectives were to determine the rate of UTI among febrile SCD children and describe the risk factors for UTI in this population. We conducted a retrospective chart review of all fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The chest X-ray is mandatory in Sickle cell patient presenting with respiratory features. The radiologic result of infiltration presenting as opacity in COVID-19 positive patients or Sickler patients indicating acute chest syndrome [5][6][7][8][9][10][11][12][13][14][15][16]. According to current study of radiological investigation, the infiltration of different lung lobe found to be in 37.2% indicate involvement of lung tissues however associated complication of covid19 pulmonary infection such as cardiac effusions in 4.6% and pulmonary embolism in 4.6%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The chest X-ray is mandatory in Sickle cell patient presenting with respiratory features. The radiologic result of infiltration presenting as opacity in COVID-19 positive patients or Sickler patients indicating acute chest syndrome [5][6][7][8][9][10][11][12][13][14][15][16]. According to current study of radiological investigation, the infiltration of different lung lobe found to be in 37.2% indicate involvement of lung tissues however associated complication of covid19 pulmonary infection such as cardiac effusions in 4.6% and pulmonary embolism in 4.6%.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the infection, hypoxia, dehydration, or acidosis inked to clinical and laboratory presentation are aggravating factors to vasoocclusive crisis [1]. Since the respiratory infection is aggravating factors to acute chest syndrome [1], the acute chest syndrome mimics clinical features and investigations of covid19 respiratory infection from mild to severe conditions [5][6][7][8][9][10][11][12][13][14][15][16]. In current study, the sickle cell anemia present with vascooclusiove pain due to covid19 infection which has been approved by nasopharyngeal swap in all cases of different days of admission with a majority of first and third days due to clinical features presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors were not able to confirm this hypothesis by analysis of urinary samples of 167 febrile children (<4 years of age) with sickle cell anemia. With 4.1% of urinary infections, the rate of urinary tract infections was as high as in non-sickle cell anemia children [ 4 ].…”
Section: Epidemiology Of Sepsis (Three Publications)mentioning
confidence: 99%
“…Urinary tract infections (UTIs) are more common in African children of the same age with SCD than in children without SCD [6][7][8][9]. Its incidence has also been reported in children living in the USA, with a diagnosis rate of 4% [9]. UTI affects the quality of life of SCD patients.…”
Section: Introductionmentioning
confidence: 99%